2020
DOI: 10.1080/02656736.2019.1711203
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided percutaneous microwave ablation of hepatocellular carcinoma in challenging locations: oncologic outcomes and advanced assistive technology

Abstract: Purpose: To assess the oncologic outcomes of the hepatocellular carcinoma (HCC) patients in challenging locations (CLs) underwent ultrasound-guided percutaneous microwave ablation (US-PMWA) and the efficacy and safety of the advanced assistive technology (AAT). Materials and methods: Data for 489 treatment-naïve patients with HCC who met Milan criteria and subsequently underwent US-PMWA were reviewed from March 2012 to November 2016. According to the distance (<5 mm) between the tumor and surrounding structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 36 publications
3
12
0
Order By: Relevance
“…In addition, multiple nodules, large tumor size and high AFP level were risk factors for poor OS. This result suggested that the tumor characteristics play a key role in the prognosis of patients, which was consistent with previous studies [24,25]. At present, imaging technologies like CEUS, CT and MRI are most commonly used to evaluate the technical effectiveness of MWA [26].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In addition, multiple nodules, large tumor size and high AFP level were risk factors for poor OS. This result suggested that the tumor characteristics play a key role in the prognosis of patients, which was consistent with previous studies [24,25]. At present, imaging technologies like CEUS, CT and MRI are most commonly used to evaluate the technical effectiveness of MWA [26].…”
Section: Discussionsupporting
confidence: 89%
“…percutaneous MWA for patients with HCC in challenging locations. The results also demonstrated that OS and RFS were not influenced by tumors whether near large vessels or not [24]. In multivariate analysis, recurrent type, multiple nodules, large tumor size and high GGT level were risk factors for poor RFS.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In thermal ablation practice, especially with USguidance, both the subcapsular lesions and the sections of the lesion close to the liver capsule are sometimes disadvantageous places for the performer in terms of approaches and manipulations (21). The physicians usually prefer to use some assistive techniques such as hydrodissection to protect the liver capsule for an undesired and extrahepatic ablation (22).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a precise and cautious operation is essential to remove these tumours in challenging locations (eg, subcapsular and perivascular locations). 9,10 Cryoablation (CRA) has become one of the most effective locoregional therapies in HCC, presenting various advantages, [11][12][13] including the lack of serious damage to large blood vessels, the development of a visual ice ball activation of cryoimmunology in cancer and the absence of an association with severe pain. Most studies have reported that CRA has comparable outcomes to radiofrequency ablation (RFA) or microwave ablation (MWA) for HCC.…”
Section: Introductionmentioning
confidence: 99%